2020
DOI: 10.1186/s13033-020-00407-1
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying and treating maternal mental health difficulties in Afghanistan: A feasibility study

Abstract: Background The disproportionately high burden of mental disorders in low- and middle-income countries, coupled with the overwhelming lack of resources, requires an innovative approach to intervention and response. This study evaluated the feasibility of delivering a maternal mental health service in a severely-resource constrained setting as part of routine service delivery. Methods This exploratory feasibility study was undertaken at two health facilities in Afghanistan that did not have specialist mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…This suggests that depression symptoms remained the same even after the war ended in Afghanistan. This nding is consistent with another study which found that psychological distress symptoms were prevalent among 75% of the national Afghan population [30], but much higher than a study among Afghan pregnant women which reported the prevalence of depression to be 60.9% [31], Compared to countries elsewhere in the world, a systematic review by Mahmud et al [32] examining depression during COVID-19 indicated that 30.5% of the global population exhibited symptoms of depression. These ndings suggest that in Afghanistan, the prevalence of depression exceeds that of the global average.…”
Section: Discussionsupporting
confidence: 85%
“…This suggests that depression symptoms remained the same even after the war ended in Afghanistan. This nding is consistent with another study which found that psychological distress symptoms were prevalent among 75% of the national Afghan population [30], but much higher than a study among Afghan pregnant women which reported the prevalence of depression to be 60.9% [31], Compared to countries elsewhere in the world, a systematic review by Mahmud et al [32] examining depression during COVID-19 indicated that 30.5% of the global population exhibited symptoms of depression. These ndings suggest that in Afghanistan, the prevalence of depression exceeds that of the global average.…”
Section: Discussionsupporting
confidence: 85%
“…The authors also highlight a high prevalence of PPD in the antenatal 36.4% and postpartum 34.3% periods among women. 29 Studies with similar high prevalence rates of PPD can also be seen in countries such as Pakistan (63%), 30 Afghanistan (60.93%), 31 Eswatini (47.4%) 32 and Croatia (45.03%) 6 and South Africa (39,93%). 33 However, the results of d 238 women (not including four women who were single or divorced/parents passed away) answered.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, while the inclusion criteria selection of only controlled trials provides more robust data, it also means that it is not a full representation of all interventions that have integrated perinatal depression and anxiety care into routine maternal care in LMICs. During full text review, additional articles describing integrated care interventions were ultimately excluded due to lack of a comparison group or lack of outcome measures (84)(85)(86)(87)(88). However, the inclusion criteria selection for controlled trials over RCTs did allow for greater study inclusion and representation of existing interventions, as was intended.…”
Section: Discussionmentioning
confidence: 99%